Teacher creativity and adaptive strategies for diverse learning styles in Islamic religious education: A case study of a pesantren-based vocational school - Sa'diyah, Nisfi Lailatul; Dasuki , Mohammad (Asatiza: Jurnal Pendidikan, 2025)
This study investigates the creativity of Islamic Religious Education (PAI) teachers in adapting teaching strategies to students’ diverse learning styles at SMK Darul Muqomah Gumukmas during the 2024/2025 academic year. Using a qualitative case study design, data were collected through classroom observations and in-depth interviews with two PAI teachers and fifteen students representing visual, auditory, and kinesthetic learning styles. Findings indicate that teachers synergized method-based and media-based adaptations; for example, kinesthetic learners were engaged through role-playing simulations of religious narratives, supported by digital animation, while visual learners benefited from slides and hand-drawn illustrations. Despite these efforts, challenges such as limited time, resources, and digital competence persisted. The novelty of this study lies in examining the intersection of learning-style theory, creative pedagogy, and Islamic religious instruction within the under-researched context of vocational education integrated with pesantren values. Based on these findings, it is recommended that professional development programs emphasize technological pedagogical content knowledge (TPACK) tailored for Islamic education, enabling teachers to creatively integrate digital tools with religious content while addressing diverse learner needs.